1975
DOI: 10.1037/0022-006x.43.5.619
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofessionals' judgments about clinical interaction problems.

Abstract: Helper-judged frequency and discomfort values were established for potentially challenging interaction situations between nonprofessional child aides and young maladapting school children. Helper discomforts were found to cluster meaningfully. Child aggression, family problems, and limit-testing behavior produced greater helper discomfort than the child's need to have the aide for himself or to be dependent. Rarely experienced situations had the highest judged discomfort ratings.Anyone who has served as a help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Each child received summary scores for aggression and for social withdrawal based on the total number of nominations received during each year. Classroom teachers rated each child's behavior by using a standard scale adapted from the Classroom Adjustment Rating Scales developed by Cowen and his colleagues (Cowen, Lorion, & Caldwell, 1975;Patterson et al, 1990). Teachers rated each item on a 5-point Likert-type scale.…”
Section: Measures Of Children's Aggressive Behavior and Social Withdrmentioning
confidence: 99%
“…Each child received summary scores for aggression and for social withdrawal based on the total number of nominations received during each year. Classroom teachers rated each child's behavior by using a standard scale adapted from the Classroom Adjustment Rating Scales developed by Cowen and his colleagues (Cowen, Lorion, & Caldwell, 1975;Patterson et al, 1990). Teachers rated each item on a 5-point Likert-type scale.…”
Section: Measures Of Children's Aggressive Behavior and Social Withdrmentioning
confidence: 99%
“…It may be that children are not expected to show extensive verbal skills in new situations (the taped interview was an intake session) and that lack of such skills is not interpreted as evidence of resistance and pathology as it is in adults. Lorion, Cowen, and Caldwell (1974) found that shy, undersocialized children had more favorable project outcomes than aggressive children; and Cowen, Lorion, and Caldwell (1975) found that helper discomfort with child clients was produced by aggressive, limit-testing behavior, rather than by shy, dependent behavior.…”
Section: Discussionmentioning
confidence: 99%